Student Reasons for Withdrawing from the University of Alberta: 1978-79 - Sartoris, Paul C.; Vanderwell, Allen R. (Canadian Journal of Counselling and Psychotherapy, 2012)
A questionnaire relating to reasons for withdrawing from the University was administered to 627 University of Alberta students during the 1978-79 winter session. Almost half the students withdrawing were in the first year of their program, with the percentage of men and women withdrawing closely paralleling their representation in the intramural population. Faculty withdrawal rates were generally lower than was the case in an earlier attrition study undertaken in 1971, these decreases possibly reflecting recent quota restrictions. In decreasing order of frequency, the reasons for withdrawing labelled by students as "relevant" were as follows: to take employment or transfer to a different educational or training program, personal reasons (such as boredom, family problems, etc.), need for a break from studies, academic problems (wrong faculty, coursework irrelevant), failing courses or not measuring up, and financial difficulties. Six other reasons were included on the questionairc but were considered relevant by relatively few respondents. Some of the implications for universities interested in lowering their attrition rate arc discussed and the need to regularly monitor attrition is recommended as a readily available index of an institution's "health."